2018
DOI: 10.1101/494351
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low acetylcholine during early sleep is important for motor memory consolidation

Abstract: The synaptic homeostasis theory of sleep proposes that low neurotransmitter activity in sleep is optimal for memory consolidation. We tested this theory by asking whether increasing acetylcholine levels during early sleep would disrupt motor memory consolidation. We trained separate groups of adult mice on the rotarod walking and skilled reaching for food tasks, and after training, administered physostigmine, an acetylcholinesterase inhibitor, to increase cholinergic tone in subsequent sleep. Post-sleep testin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 102 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…Behavioral data from both human subjects ( 38 , 39 ) and animal models ( 55 ) demonstrate that reduced acetylcholine signaling is essential for the benefits of sleep for memory consolidation ( 37 39 ). MS cholinergic neurons send the majority of their output to the hippocampus, although a smaller subset provide cholinergic input to neocortical sites, including entorhinal and primary sensory cortices ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral data from both human subjects ( 38 , 39 ) and animal models ( 55 ) demonstrate that reduced acetylcholine signaling is essential for the benefits of sleep for memory consolidation ( 37 39 ). MS cholinergic neurons send the majority of their output to the hippocampus, although a smaller subset provide cholinergic input to neocortical sites, including entorhinal and primary sensory cortices ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, machine learning approaches combined with in vivo neurochemical data demonstrated that concentrations of neurotransmitters such as ACh and norepinephrine in prefrontal cortex can predict the levels of cortical and behavioral arousal [22]. Low levels of ACh during NREM sleep have been suggested to enhance synapse formation and episodic/motor memory consolidation mechanisms [23,24].…”
mentioning
confidence: 99%